PENGATURAN PERKAWINAN PADA GELAHANG DALAM AWIG-AWIG DESA PAKRAMAN - Sudantra, I Ketut; Sukerti, Ni Nyoman; Atu Dewi, A.A. Istri Ari (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 3 (2015), 2015)
This article was written based by result of normative legal research about the regulation of pada gelahang marriage on customary law that created by customary law society of desa pakraman in Bali. That research was aimed to identify legal norms in awig-awig desa pakraman that regulate about pada gelahang marriage. From that research’s result, it was known that aspect of matrimonial law has been regulated in awig-awig, whic is on certain chapter that regulate family law. That chapter titled Sukerta Tata Pawongan, that regulate the legal aspects about marriage, divorce, lineage, and inheritance. Although, the research result aslo shown that on nine awig-awig desa pakraman researched, only one that regulate about pada gelahang marriage, which is Awig-Wig Desa Pakraman Gadungan (Tabanan). The regulation is rather ambigious, only regulate about recognition of pada gelahang marriage existance, without any further regulation about requirements, procedure or it’s legal consequences.
Keywords: awig-awig desa pakraman; customary law society; pada gelahang marriage